011. Solid-Pseudopallary Tumor of Pancreas in Childhood, A Case Report - Gunawan, Andrey; Ariyanta, Kadek Deddy (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p011, 2024)
Background : Solid-pseudopapillary tumor of the pancreas (SPT) is an exceptionally rare neoplasm in children. Its origin remains enigmatic. It occurs most frequently in young females within the second or third decade of life with only a small minority concerning children. Frequently described as low malignant potential tumors, surgical resection remains the main treatment. Case : The authors present a case of a SPT diagnosed in a 12-year-old with vomiting and abdominal pain localized to the right upper quadrant 2 week before admission to hospital. The patient also became yellowish since 1 week before. The patient undergo MRI scans and showed the presence Heterogeneous solid mass with components of necrosis and bleeding in it in the head of the pancreas. The patient undergone surgery with the histomorphology result Solid Pseudopapillary Neoplasm of pancreas, low grade malignancy. Conclusion: SPT is a rare differential diagnosis of a pancreatic mass in children. It is mandatory to establish this diagnosis since complete surgical removal of the tumor even in case of metastases or local invasion offers an excellent prognosis